(NmAKROSKOPI^ESKAQ \LEKTRODINAMIKA (B/s - (NgALICKIJ(B, (NwIKTOR mIHAJLOWI^s; (NeRMA^ENKO(B, (NwALERIJ mIHAJLOWI^s ((NmOSKWA (B:s (NwYS[(B. (N[K(B,s, 1988)
(NbIBLIOGR(B.: (NS(B. 159 (5 (NNAZW(B.)s
Keywords: (NkWANTOWAQ \LEKTRODINAMIKAs; (NrASPROSTRANENIE W SPLO[NYH SREDAHs; (N|LEKTROMAGNITNYE WOLNYs